I think its 36, i'm not sure.
It is read as a minus b minus c whole square. The (a - b - c)2 formula is expressed as (a - b - c)2 = a2 + b2 + c2 - 2ab + 2bc - 2ca.
Use the substitution method:
2x - 6y = -12
x - 2y = -8
Then x = 2y - 8
Substitute in the first equation:
2(2y - 8) - 6y = -12
4y - 16 - 6y = -12
-2y = 4
y = -2
Now substitute y in one of the two equations given you prefer:
For example x-2*(-2) = -8
x + 4 = -8
x = -12
The solutions are x = -12 and y = -2
<span>3x^2 + 18x + 15 = 0
15 + 18x + 3x2 = 0
3(5 + 6x + x2) = 0
</span>3((5 + x)(1 + x)) = 0
5 + x = 0
5 + -5 + x = 0 + -5
Combine like terms: 5 + -5 = 0
0 + x = 0 + -5
x = 0 + -5
x = -5
<span>--------------------------------------------
1 + x = 0
x=-1
-5,-1 </span>
English Alphabet = e
Greek Alphabet = g
The English Alphabet has 20 letters more than one-fourth the numbers of letters in the greek alphabet: 1/4g + 20 = e
The English has 26 letters.
Plug in 26 for e
1/4g + 20 = 26
Isolate the g, do the opposite of PEMDAS. Note the equal sign. What you do to one side you do to the other.
Subtract 20 from both sides
1/4g + 20 (-20) = 26 (-20)
1/4g = 26 - 20
1/4g = 4
Multiply 4 to both sides to isolate the g
1/4(4)g = 4(4)
g = 4(4)
g = 16
The Greek Alphabet has 16 letters
hope this helps